(untitled) (Journal of Shaheed Suhrawardy Medical College, 2013)
Endometriosis is a common gynaecological condition and presents mainly with involvement of the pelvic organs. However umbilical endometriosis is uncommon. A correct differential diagnosis can be difficult and the use of epiluminescence and MRI is suggested for the accuracy of preoperative diagnosis. This case report was experienced at a tertiary care hospital at Dhaka city. The patient was 39 years old multigravid woman presented with umbilical swelling and pain during menstruation for last 1year with cyclical bleeding from the umbilical region for last 4 months. The patient had regular menstrual bleeding since the time of menarche. The patient had no previous history of endometriosis, dysmenorrhea or dyspareunia. Physical examination showed a hyperpigmented tender paraumbilical swelling with bloody discharge through umbilicus. An accurate anamnesis and clinical examination together with the use of high resolution ultrasonography and fine needle aspiration cytology led to an accurate pre-operative diagnosis of umbilical endometriosis. The surgical approach to umbilical endometriosis represented an important step in achieving a satisfying result. The lesion to be excised and adequate umbilical repositioning was done. The patient was asymptomatic at the follow-up visit (12 months after surgery), however, nevertheless warned of the risk of recurrence. A natural-looking umbilicus was observed in cases with minimal visible scars DOI: http://dx.doi.org/10.3329/jssmc.v4i2.14423 J Shaheed Suhrawardy Med Coll, 2012;4(2):65-67